(3TQM YbGFO GdfSajs - (3GdJaJGRGfj, SYO GdOjf, eSYhO Hf YeQ Hf YHO Gddg, J(B793(3g`s ((3SeQbfOs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdeJhMO HLdGd PGJg hHYO aEf eHfi Yde GdTQGFY hGdCMcGe hCSGS bhGYO YbGjO GdESdGe gh Yde GdJhMjO hCf GdeNJUQ GdeSei HGdYbGjO ddTjN YeQ GdfSaj jTJed ef gPg Gdaf aMGhdJ Cf CTQMgs
(3BNQgG (B:s
(3hGdYdh EfeG gh aj CeQ GdJLQO hEXgGQ GdBKGQ GdbhjI dG aj eWdb GdTQa hGdceGd adG OdGdI Ydi CaVdjI GdedGFcIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 219s
(3eYLe GdeDdajf (B3 / 849s
(3cTa GdXfhf (B2 / 1145s
(3TPQGJ GdPgH (B6 / 309s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds